Uma nova forma aberta do princípio do máximo fraco e estimativas de autovalores para uma classe de operadores diferenciais elípticos - (:unkn) unknown (Universidade Federal do Amazonas, 2015)
This view is composed of two parts. Initially we present an open way the principle of the weak maximum for a specific class of elliptic operators with applications hypersurface height estimates immersed mean curvature k constant warped products, whose base is a line interval. Later, we display estimates involving eigenvalues of an operator in n-divergently in limited domains with boundary conditions of Dirichlet, a Riemannian manifold Full and found a sharp estimate, compared to asymptotic formula Weyl, to the eigenvalues of the n-Laplacian operator
Keywords: Problema de Dirichlet; Dirichlet problem; Dirichlet, Problemas de; CIÊNCIAS EXATAS E DA TERRA: MATEMÁTICA: GEOMETRIA E TOPOLOGIA: GEOMETRIA DIFERENCIAL